1963
DOI: 10.1161/01.cir.27.5.929
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Extent and Severity of Atherosclerosis in the Coronary and Cerebral Arteries

Abstract: A study of correlation of the extent and severity of atherosclerosis in the coronary and cerebral arteries and between their individual branches has been undertaken in 200 consecutive medicolegal autopsies. The coronary atherosclerosis developing first in the second decade appears about 20 years earlier than the cerebral atherosclerosis. There is, however, a significant correlation between the coronary and cerebral arterial beds. There is a significant interbranch relationship within the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 6 publications
5
51
2
Order By: Relevance
“…28 " 34 However, in vivo evidence points to the association of atherosclerotic involvement in the two arterial circulations. First, most patients with measurable carotid disease or symptoms of carotid disease die of complications of coronary atherosclerosis, not of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…28 " 34 However, in vivo evidence points to the association of atherosclerotic involvement in the two arterial circulations. First, most patients with measurable carotid disease or symptoms of carotid disease die of complications of coronary atherosclerosis, not of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…12) On the other hand, autopsy studies have shown a strong correlation between carotid and coronary atherosclerosis and parallel findings were found in several clinical studies. [13][14][15][16][17][18] However, the clinical importance of coexisting CAS in patients with MAC, in terms of its implications on the frequency and severity of CAD, has not been extensively studied. In this study, we investigated how the incidence and extent of CAD are affected by the coexistence of carotid atherosclerosis in patients with MAC as compared to those without.…”
mentioning
confidence: 99%
“…1,2) Since arteriosclerosis may affect the aorta and coronary arteries simultaneously, 3) it has been shown that aortic stiffness and distensibility may be markers of coronary events. 4,5) It is inevitable that the arterial pulse is affected by the changes in aortic stiffness and distensibility.…”
mentioning
confidence: 99%